Matariki : a monograph (Vol 1 No 7) - Te Mata o Te Tau, The Academy for Māori Research and Scholarship (Te Mata o Te Tau, Office of the Deputy Vice Chancellor Māori, Massey University, 2024)
Our Twentieth Anniversary was a memorable occasion, celebrated at Government House, Wellington, in regal style through the manaakitanga of Dame Cindy Kiro, our twenty-second Governor-General, the first Māori woman to hold the position, and a Foundation Fellow of Te Mata o te Tau. Her Excellency’s welcoming address opens this monograph. Our keynote speaker was Emeritus Professor Sir Mason Durie, both a Foundation Fellow and Foundation President (Puna Tātai Hono) of the Academy. This Monograph – the seventh in the Matariki Series – celebrates that event and also profiles the Foundation Fellows. It begins with the Governor-General’s address, followed by a typically thought-provoking paper on Te Tiriti-o-Waitangi and Aotearoa New Zealand, by Professor Sir Mason Durie. Honouring our Foundation Fellows, we provide extracts from their doctoral theses, together with the abstracts of those new fellows who graduated in 2023.--From Foreword
Commemorating the twentieth anniversary of Te Mata o Te Tau, The Academy for Māori Research and Scholarship at Massey University.